X-ray structure and theoretical studies on a palladium(II) Schiff base complex - Akbari, Alireza; Ahmadi, Mehdi; Takjoo, Reza; Heinemann, Frank Wilhelm (Journal of Coordination Chemistry, 2013)
Treatment of N,N-bis(salicylidene)-1,2-cyclohexanediamine (H2L) with PdCl2 in the presence of triethylamine afforded [Pd(N2O2)]. Recrystallization in chloroform and acetonitrile (1:1) gave suitable crystals for X-ray crystallography. The solid-state structure shows that the environment around palladium is square planar. The structural parameters of the molecule obtained by density functional theory (DFT) calculation in the gas phase and by X-ray diffraction are compared. The Pd(II) Schiff base complex adopts planar geometry by DFT calculation. The coordination site structural parameters, which are obtained from geometry optimization calculation, are close to those from X-ray crystallographic data. The spectral properties such as vibrational frequencies, chemical shifts, electronic excitation and the natural bond orbital analyses of Pd(Salen) are calculated, analyzed and compared with experimental data.
Keywords: Palladium(II) complex; Crystal structure; Schiff base; DFT calculation